The Rediscovery of Machiavelli in Napoleon’s Germany. Heinrich von Kleist and his Contemporaries - Robertson, R (Università degli Studi di Trieste, 2016)
Successive defeats by Napoleon’s armies, and the occupation of Prussia by the French after the battle of Jena, inspired a new interest in Machiavelli among German thinkers. Hegel, in his unpublished essay on the German constitution, compared the fragmented state of Germany to that of Machiavelli’s Italy. Fichte, in his essay on Machiavelli, drew a comparison with the French invasion of Italy in 1494, and argued that Germany needed to be unified under a powerful ruler, as Machiavelli had recommended for Italy. He and F.L. Jahn were inspired by Machiavelli’s concept of the democratic nation composed of patriotic citizens who were always ready to fight for it. Finally, Kleist, who probably absorbed Machiavellian ideas indirectly via Rousseau, celebrated the unscrupulous Machiavellian liberator in Die Herrmannschlacht, gave a more critical portrayal of Machiavellian statecraft in Prinz Friedrich von Homburg, and, in the latter play, developed the idea of the military republic united by patriotism.